Recent trends and climatic perspectives of hailstorms frequency and intensity in Tuscany and Central Italy - F. Piani; A. Crisci; G. De Chiara; G. Maracchi; F. Meneguzzo (Natural Hazards and Earth System Sciences, 2005)
The damages from climatic extremes have dramatically increased in the last decades in Europe, as likely outcomes of climate change: floods, droughts, heat waves and hailstorms have brought local as well as widespread damages to farmers, industry, infrastructures and society, to insurance and reinsurance companies; in this work we deal with the hailstorm hazard. The NCEP-NCAR Reanalysis (2.5 by 2.5° lat-lon) over the Italian area and the hailstorm reports at several sites are used to identify few forcings for hailstorms; statistical relationships linking forcings and hailstorm frequencies are derived. Such relationships are applied to the same forcings derived from the CGCM2-A2 climate scenario provided by the Canadian Centre for Climate modeling and analysis (CCCma; resolution approximately 3.75 by 3.75° lat-lon), to evaluate the expected changes of the frequency of hailstorms. The time series of the forcings from the NCEP-NCAR Reanalysis and the CCCma climate scenario in the past decades are compared in order to assess the reliability and accuracy of the predictions of the future hailstorm hazard. It is shown that the climate scenario provides a fairly faithful representation of the past trends of the forcings relevant to the hailstorms frequency and that such quantity, hence the hailstorm hazard, is growing and will likely grow in the future over the limited area taken into consideration in this study.